Application of Aleppo pine extract for skin burn treatment - Salhi, Najoua; El Guourrami, Otman; Balahbib, Abdelaali; Rouas, Lamiae; Moussaid, Siham; Moutawalli, Amina; Benkhouili, Fatima Zahra; Ameggouz, Mouna; Ullah, Riaz; Alotaibi, Amal; Bouyahya, Abdelhakim; Tan, Ching Siang; et al. (SAGE Publications, 2024)
Objective: To investigate the Pinus halepensis extracts and determine its healing and antibacterial effects, and to evaluate the treatment of skin burns.